Fekete-Szegö Inequalities for Certain subclasses of p-Valent Functions of Complex Order Associated with Fractional Derivative Operator - Amsheri, Somia; Alnajjar, L. (مجلة العلوم الإنسانية والتطبيقية, 2019)
In the present paper, we obtain Fekete-Szegö inequalities and sharp bounds for some subclasses of analytic and p-valent functions in the open unit disk defined by certain fractional derivative operator.